2019
DOI: 10.3390/s19235179
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of the EncephaLog Smartphone Application for Gait Analysis

Abstract: Gait disorders and falls are common in elders and in many clinical conditions, yet they are typically infrequently and subjectively evaluated, limiting prevention and intervention. Completion-time of the Timed-Up-and-Go (TUG) test is a well-accepted clinical biomarker for rating mobility and prediction of falls risk. Using smartphones’ integral accelerometers and gyroscopes, we already demonstrated that TUG completion-time can be accurately measured via a smartphone app. Here we present an extended app, Enceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
(61 reference statements)
0
22
0
Order By: Relevance
“…This observation should be replicated in the presence of a control population, which is currently missing. To this regard, the EncephaLog TM TUG test has been already validated against other medical devices in dedicated laboratories and compared to GAITRite pressure walkaway, Vicon 3D cameras and wearables providing a reliable biomarker in both PD and healthy volunteers (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…This observation should be replicated in the presence of a control population, which is currently missing. To this regard, the EncephaLog TM TUG test has been already validated against other medical devices in dedicated laboratories and compared to GAITRite pressure walkaway, Vicon 3D cameras and wearables providing a reliable biomarker in both PD and healthy volunteers (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Standard movement performance tests (PTs) were selected to assess the chosen fitness components and incorporated into a smartphone application (EncephaLog TM ) developed by Montfort Brain Monitor Ltd. The EncephaLog TM has previously been validated for the remote evaluation among patients with movement disorders [28]. The application was designed to present a user-friendly fitness test protocol on the smartphone, guiding the participants through the fitness tests with audiovisual cues and instructions, while simultaneously measuring and recording the test result data.…”
Section: Methodsmentioning
confidence: 99%
“…The sway can then be evaluated either by measuring the shift in the center of pressure (COP) by using a dedicated sensor array (e.g., [29, 30]), which is correlated to the shift in COM, or by directly measuring the accelerations of the COM itself [31]. As the sternum is above the COM, it was demonstrated that measuring the participant’s motion at that height yields a more sensitive measurement of sway changes, one that is correlated to other methods of measuring the sway from both the COP and COM [28]. Thus, 5 relevant DMs were selected: average linear acceleration assessed in meter per second squared (m/s 2 ), which is generated from the accelerometer in ML and AP directions (which are correlated to the acceleration of the COP and shift in the COM), and angular (radial) velocity assessed in radians per second (rad/s), which is generated from the gyroscope in the ML, AP, and SI (superior-inferior) directions and measures the same sway shifts in angles, thus offering a complementary view to the participant’s balance.…”
Section: Methodsmentioning
confidence: 99%
“…Although consumer grade technology is widely available, only Encephalog was commercially available as a complete solution for researchers gathering metrics of interest (Tchelet et al 2019). This highlights that further progress is required for many of these fully remote and smartphone-based tools.…”
Section: Wearables -Othermentioning
confidence: 99%